1493. Effect of HIV Status on Early Syphilis Treatment Response in the Era of Combination Antiretroviral Therapy. (26th November 2018) - King, Helen; Tilghman, Winston; Prakash, Katya; Kofman, Aaron; Katsivas, Theodoros; He, Feng; Jain, Sonia; Hicks, Charles
Abstract: Background: Rates of incident early syphilis are increasing and HIV-coinfection is common. Syphilis treatment for HIV-positive individuals does not differ from that of the general population, although data published prior to combination antiretroviral therapy (cART) suggest that HIV-infected persons may be less likely to achieve expected serologic responses to treatment (SRT). Methods: We conducted a cohort study of early syphilis diagnosed in a large HIV clinic and a public sexually transmitted diseases (STD) clinic in San Diego. SRT was defined as a fourfold or greater decline in rapid plasma reagin (RPR) titer following syphilis treatment. We compared SRT at 6 and 12 months post-treatment between HIV-infected and HIV-uninfected persons. Results: Of 1, 239 early syphilis cases reviewed, 742 (61%) were included in the analysis. Reasons for exclusion included lack of follow-up RPR ( n = 454), nonreactive RPR at syphilis diagnosis ( n = 33), and incomplete data ( n = 10). Of those analyzed, 533 (72%) were HIV-positive; 168 (23%) HIV-negative; HIV status was unknown for 41 (5%). Overall, 449 (60%) and 657 (89%) of analyzed cases achieved SRT 6 and 12 months after treatment, respectively. HIV-positive cases were less likely to achieve SRT at 12 months than HIV-negative cases (464/533 [87%] vs. 160/168 [95%], P = 0.003, Figure 1), as were early latent syphilis cases (285/348 [82%]) vs. primary (102/117 [92%]) and secondary syphilis (264/277 [94%]) (Table 1). Conclusion: In this cohort of early syphilis cases, most achieved SRT within 12 months of treatment, but only 60% achieved SRT within 6 months. Significantly lower 12-month SRT responses were seen in HIV-positive compared with HIV-negative persons and in early latent compared with primary and secondary syphilis. The impact of cART use, viral suppression, and treatment choice on outcomes is being analyzed. Disclosures: All authors: No reported disclosures.